Os cursos de licenciatura em Ciências Biológicas de universidades estaduais do Ceará: os processos de reformulações curriculares a partir de determinantes legais e das narrativas dos coordenadores - Pessoa, Camylla Alves do Nascimento (2022)
This work starts from the thesis that the processes of curricular reformulation of Licentiate Degree courses in Biological Sciences at Universidade Estadual do Ceará were driven by legal alternatives, curricular theorizations and political-pedagogical practices. It aimed to understand the process of curricular reformulation of the degree courses in Biological Sciences at UECE/Itaperi, UECE/FAEC and URCA in response to Resolution No. 2/2015, based on the coordinators' narratives. The research was developed through a Multiple Case Study and was based on the epistemological framework related to critical curriculum theories. Data collection was based on document analysis and oral narratives. The analysis of the pedagogical design of the courses shows that this document was reformulated to meet the legal dictates relevant to the new National Curriculum Guidelines for the Initial and Continuing Training of Basic Education Teachers, with the main change being aspects related to the BNCC. This analysis revealed that the Degree in Biological Sciences courses at UECE/ FAEC and UECE/Itaperi made changes to their curriculum to comply with the BNCC and the reformulation of the URCA course is not aligned with the BNCC. Regarding oral narratives, the coordinators understand the curricular restructuring as a challenging moment, which impacted the reality of the Biological Sciences Course, meaning changes in the training structure, understood in the case of the Degree in Biological Sciences at UECE/FAEC as a decision to form only teachers, moving away from a generic training for bachelors and licentiates. The Licentiate in Biological Sciences at UECE/Itaperi, on the other hand, presents the curricular flexibility that seeks to articulate the theoretical and practical part within the disciplines as a differential mark, this flexibility was designed to offer the theoretical part common to the Licentiate and Baccalaureate modalities. . In the case of URCA, it seeks training that is closer to the demands linked to daily teaching activities. To meet these changes, it was possible to identify relationships of power disputes for the adequacy of workload. The processes of curricular reformulation of the investigated cases constitute a complex movement, in which the texts of the reformulations represent a hybrid and provisional product, which incorporated the initial training and the power relations of its actors.